2020
DOI: 10.14254/1800-5845/2020.16-1.14
|View full text |Cite
|
Sign up to set email alerts
|

Human Resource Management Practice in Lithuania: Evidences and Challenges

Abstract: As human resources have been already recognized as the most valuable factor for organizational success, HRM in order to cope with new challenges has to focus more and more attention to the choice and application of up-to-date practices that would allow the most efficient use of the human resources of organizations. The purpose of this article is to define the level of usage of different HRM practices in business companies in Lithuania and to assess the perception of their effectiveness by HR specialists and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…What is a reward differs between individuals and context, it is not only wages but can also be, for example, esteem, recognition, job security and the possibility of promotion (Spanier et al 2014). Performance appraisals, which are necessary to determine rewards, can be conducted more effectively if the job definition and its strategic purposes are clear (Tamasevicius et al 2020). Solomonidou and Katsounari (2020) found that excessive workload, working overtime, role ambiguity, role conflict, ethical dilemmas, unmet personal expectations and a negative public perception of the profession were sources of stress among social workers.…”
Section: Well-being and Job Satisfactionmentioning
confidence: 99%
“…What is a reward differs between individuals and context, it is not only wages but can also be, for example, esteem, recognition, job security and the possibility of promotion (Spanier et al 2014). Performance appraisals, which are necessary to determine rewards, can be conducted more effectively if the job definition and its strategic purposes are clear (Tamasevicius et al 2020). Solomonidou and Katsounari (2020) found that excessive workload, working overtime, role ambiguity, role conflict, ethical dilemmas, unmet personal expectations and a negative public perception of the profession were sources of stress among social workers.…”
Section: Well-being and Job Satisfactionmentioning
confidence: 99%
“…knowledge in general) (Tarabasz et al, 2018;Dzimińska et al, 2020;Sułkowski et al, 2019). Many other authors have insisted on this (Sedziuviene & Vveinhardt, 2018, p. 226;Mikalauskiene & Atkociuniene, 2019;Tamasevicius et al, 2020;Tóth et al, 2020), particularly, investigating effects of intellectual capital restoring considering the impact of external migration (Bilan et al, 2019;Mishchuk et al, 2019;). Let's remember e.g.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Human resources have a special nature and uniqueness [7,8]. They are the key factor [9,10], the most valuable factor [11,12], but also the most costly production factor [13]. They cannot be compared to other resources such as production equipment, money, energy, or information.…”
Section: Introductionmentioning
confidence: 99%